Three Generations - Wankowich, Melchior (Toronto Canadian-Polish Research Institute in Canada, 1973)
Turning Melchior Wankowiczs novel about Polish immigrants who arrived in Canada at the beginning of this century over to the reader, it seems relevant to introduce the author and the background of his novel.
Keywords: Literature